Development and evaluation of prediction equations for methane emission from Nellore cattle - Pires Sobrinho, Tatiana Lucila; Branco, Renata Helena; Magnani, Elaine; Berndt, Alexandre; Canesin, Roberta Carrilho; Mercadante, Maria Eugênia Zerlotti (Editora da Universidade Estadual de Maringá - EDUEM, 2019)
ABSTRACT. Dry matter intake (DMI), nutrient intake and enteric CH4 emission were evaluated in 48 Nellore cattle (392 ± 27 days of age). Equations were generated from intake data and evaluated using root mean square prediction error (RMSPE), and validated by cross-validation. Equations that included DMI and hemicellulose intake (HEMI) [C H4 M Jd- 1 = 4.08 ± 1.65 + 11.6 ± 2.34 D M I k gd- 1 - 33.4 ± 7.21 H E M I ( k gd- 1 ) ]; DMI and total carbohydrate intake (TCHI) [ C H4 M Jd- 1 = 5.26 ± 1.69 - 6.3 ± 1.47 D M I k gd- 1 + 8.8 ± 1.81 T C I k gd- 1 ]; metabolizable energy intake (MEI) and cellulose intake (CELI)[ C H4 M Jd- 1 = 5.16 ± 1.72 - 0.13 ± 0.048 M E I M Jd- 1 + 7.37 ± 1.53 C E L I k gd- 1 ], and non-fiber carbohydrate intake (NFCI) [ C H4 M Jd- 1 = 3.14 ± 1.48 + 3.65 ± 1.05 N F C I k gd- 1 ] resulted in the lowest RMSPE (14.3, 14.1, 14.3 and 14.7%, respectively). When literature equations were evaluated using our database, the most accurate predictions were obtained with equations that included DMI and lignin intake (RMSPE = 15.27%) and MEI, acid detergent fiber intake and lignin intake (RMSPE = 15.7%). The mean error of predicting enteric CH4 emission with the equations developed in this study based on DMI and nutrient intake is 17% and the most accurate predictions are obtained with equations including DMI, carbohydrate intake and MEI.
Keywords: beef cattle; dry matter intake; greenhouse gas; prediction; sulfur hexafluoride